A grain boundary and surface supported noble metal catalyst, and a preparation method and application thereof

CN116618046BActive Publication Date: 2026-10-16GUOKE RE ADVANCED MATERIALS CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210135505.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-14
Publication Date
2026-10-16
Estimated Expiration
2042-02-14

AI Technical Summary

Technical Problem

目前,商业化DOC催化剂存在很多缺点,如高温时贵金属易团聚失活和反应温度高等(Caliskan H,Mori K.Energy,2017,128:128-144)

Benefits of technology

[0033] In summary, this invention provides a grain boundary and surface-supported noble metal catalyst, its preparation method, and its application. In the catalyst, noble metal G is dispersed at the grain boundaries and surfaces of alumina and/or rare earth manganese-zirconium composite oxides, forming a multiphase interface. This achieves the following beneficial technical effects: First, the multiphase interface has greater steric hindrance and stronger anchoring effect, which can inhibit the high-temperature migration, aggregation, and growth of noble metals, improve the high-temperature stability and catalytic performance of noble metals, and reduce the amount of noble metal used. Second, the multiphase interface has a synergistic catalytic effect, which can reduce the lattice oxygen activation energy and increase the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116618046B_ABST
    Figure CN116618046B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of grain boundary and surface load noble metal catalyst and its preparation method and application, the noble metal is dispersed at the grain boundary and surface of aluminium oxide and / or rare earth manganese zircon composite oxide, forms multiphase interface, obtains the following beneficial technical effect: first, the multiphase interface has greater steric hindrance and stronger anchoring effect, can inhibit the high temperature migration, agglomeration and growth of noble metal, improve the high temperature stability and catalytic performance of noble metal, reduce the amount of noble metal;Second, the multiphase interface has synergistic catalytic effect, can reduce lattice oxygen activation energy and increase the number of active oxygen, improve NO oxidation rate and low-temperature catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of supported noble metal catalysts, and particularly to a grain boundary and surface supported noble metal catalyst and a honeycomb noble metal catalyst, as well as their preparation methods and applications. Background Technology

[0002] In recent years, lean-burn engines (diesel and gasoline engines) have received widespread attention due to their higher fuel economy and lower greenhouse gas emissions. However, lean-burn engines emit NO... x NO, CO, and HC, among others, seriously endanger human health. Currently, governments worldwide are imposing increasingly stringent environmental regulations on diesel vehicle exhaust. From a reaction mechanism perspective, HC and CO are easily oxidized and removed under aerobic conditions, while NO... x The reaction is complex, requiring the development of highly efficient catalysts with high oxygen storage capacity and high activity at low temperatures to achieve effective elimination. At high speeds, diesel vehicle exhaust temperatures can reach over 600°C, necessitating catalysts that maintain high activity even under these conditions. Existing catalysts, made of precious metals, tend to agglomerate at high temperatures, exhibiting poor dispersibility and failing to effectively treat diesel exhaust, thus causing environmental pollution. Therefore, developing highly stable and highly active catalysts for diesel NOx is crucial. x The development of highly efficient catalysts for exhaust gas purification is urgently needed.

[0003] Diesel oxidation catalysts (DOC) have attracted much attention in recent years. DOC has strong NO oxidizing properties and can greatly improve the NO reduction performance of SCR at low temperatures. x Conversion rate (Russell A, Epling W S. Catalysis Reviews, 2011, 53(4):337-423). Currently, commercially available DOC catalysts have many drawbacks, such as the easy agglomeration and deactivation of noble metals at high temperatures and high reaction temperatures (Caliskan H, Mori K. Energy, 2017, 128:128-144). Therefore, research on highly dispersed noble metals and highly active DOC catalysts has become a key focus of diesel engine aftertreatment systems. In order to obtain higher NO catalytic oxidation performance, it is essential to develop a highly stable and highly active DOC catalyst. Summary of the Invention

[0004] Based on the above-mentioned situation of the prior art, the purpose of the present invention is to provide a grain boundary and surface supported noble metal catalyst, preparation method and application, wherein the noble metal is uniformly dispersed at the grain boundaries and surface of alumina and / or rare earth manganese zirconium composite oxide to form a multiphase interface, which can inhibit the high-temperature migration, agglomeration and growth of noble metal, improve the high-temperature stability and catalytic performance of noble metal, reduce the amount of noble metal used, and can reduce the lattice oxygen activation energy and increase the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity.

[0005] To achieve the above objectives, according to a first aspect of the present invention, a grain boundary and surface-supported noble metal catalyst is provided, the catalyst comprising a noble metal G, alumina and / or a rare earth manganese zirconium composite oxide, wherein the noble metal G is dispersed at the grain boundaries and surface of the alumina and / or the rare earth manganese zirconium composite oxide, and the rare earth manganese zirconium composite oxide has the general chemical formula RE. a Mn b Zr c M d O (2-δ) D β ;in,

[0006] RE represents rare earth elements, M represents cationic dopant elements, and D represents anionic dopant elements.

[0007] 0.1≤a≤0.5, 0.05≤b≤0.3, 0.2≤c≤0.8, 0≤d≤0.2, 0≤δ≤0.1, 0≤β≤0.1, a+b+c+d=1.

[0008] According to a second aspect of the present invention, a honeycomb noble metal catalyst is provided, the catalyst comprising a honeycomb support, a noble metal G, and an active coating, wherein the active coating contains alumina and / or rare earth manganese zirconium composite oxide RE. a Mn b Zr c M d O (2-δ) D β The noble metal G is dispersed at the grain boundaries and surface of the active coating; wherein,

[0009] RE represents rare earth elements, M represents cationic dopant elements, and D represents anionic dopant elements.

[0010] 0.1≤a≤0.5, 0.05≤b≤0.3, 0.2≤c≤0.8, 0≤d≤0.2, 0≤δ≤0.1, 0≤β≤0.1, a+b+c+d=1.

[0011] Furthermore, the rare earth manganese zirconium composite oxide accounts for 0-100% of the total mass of the active coating, preferably 30-70%.

[0012] Furthermore, the noble metal G at the grain boundaries and surface is in a metallic state, or in both a metallic and oxidized state.

[0013] Furthermore, the precious metal G includes one or more of Pt, Pd, Rh, Ir, Os, Ru, Au and Ag, preferably one or more of Pt, Pd, Rh and Ru, and more preferably a combination of Pt and Pd.

[0014] Furthermore, the rare earth element RE includes one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc; preferably one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Yb, and Y; the doping element M is one or more of transition metal elements, alkaline earth metal elements, and Al, Si, and Sn; the doping element D includes one or more of anions N, P, and F.

[0015] Furthermore, the transition metal element is one or more of Fe, Co, Ni, Cu, Zn, Ti, Hf, V, Cr, Nb, Mo and W, preferably one or more of Fe, Co, Ni, Cu and Hf; the alkaline earth metal element is one or more of Mg, Ca, Sr and Ba, preferably one or more of Sr and Ba.

[0016] Furthermore, the loading of noble metal G in the catalyst is 0.01%-2% by mass, preferably 0.1%-1%.

[0017] Furthermore, the loading of noble metal G in the catalyst is 0.03-2.0 g / L, preferably 0.15-1.5 g / L.

[0018] Furthermore, the honeycomb carrier is made of porous ceramic or metal. Furthermore, the honeycomb carrier can be one or more of cordierite, cordierite-alumina, silicon nitride, silicon carbide, alumina-silica-magnesium oxide, zirconium silicate-sillimanite, magnesium silicate, and aluminum silicate.

[0019] According to a third aspect of the present invention, a method for preparing a grain boundary and surface-supported noble metal catalyst as described in the first aspect of the present invention is provided, comprising the steps of:

[0020] S1. Mix rare earth manganese zirconium composite oxide and / or alumina with liquid salt of noble metal G evenly and then dry.

[0021] S2. Perform one or two heat treatments on the product obtained in step S1.

[0022] S3. The product obtained in step S2 is calcined once or twice in air or a reducing atmosphere to obtain rare earth manganese zirconium composite oxide and / or alumina grain boundary and surface supported noble metal catalyst.

[0023] According to a fourth aspect of the present invention, a method for preparing a honeycomb-type noble metal catalyst as described in the second aspect of the present invention is provided, wherein the honeycomb-type noble metal catalyst is coated with one or more coating materials in steps or sections, wherein the coating material is one or two of alumina, rare earth manganese zirconium composite oxide, alumina with noble metals loaded at grain boundaries and on the surface, rare earth manganese zirconium composite oxide with noble metals loaded at grain boundaries and on the surface, and a mixture of rare earth manganese zirconium composite oxide with noble metals loaded at grain boundaries and on the surface and alumina, comprising the steps of:

[0024] A1. The coating material is mixed evenly with adhesive, acidity regulator and water through one or more steps to prepare a coating slurry;

[0025] A2. Apply the coating slurry obtained in step A1 to the honeycomb carrier in one or more steps, or apply it to the honeycomb carrier in sections or layers, and then dry it.

[0026] A3. The product obtained in step A2 is heat-treated and / or calcined in air or a reducing atmosphere to obtain a honeycomb noble metal catalyst.

[0027] According to a fifth aspect of the present invention, a method for preparing a honeycomb-type noble metal catalyst as described in the second aspect of the present invention is provided, wherein rare earth manganese zirconium composite oxide and / or alumina, noble metal G liquid salt, acidity regulator, binder and water are mixed uniformly in one or more steps to prepare a coating slurry, the slurry is coated onto a honeycomb carrier in one or more steps, or coated onto the honeycomb carrier in sections or layers, and then dried, and then the dried honeycomb carrier is heat-treated and / or calcined under a reducing atmosphere to obtain a honeycomb-type noble metal catalyst.

[0028] Furthermore, the heat treatment temperature is 200-750℃ and the heat treatment time is 0.5-24h; preferably, the heat treatment temperature is 400-700℃ and the heat treatment time is 1-12h.

[0029] Furthermore, the calcination temperature is 400-850℃ and the time is 0.5-24h; preferably, the calcination temperature is 450-750℃ and the time is 1-12h.

[0030] Furthermore, the liquid salt of the noble metal G includes one or more of the following: molten salts or aqueous solutions of chlorides, nitrates, acetates, and citrates.

[0031] Furthermore, the reducing atmosphere includes one or more of CO and H2.

[0032] According to a sixth aspect of the invention, the catalysts provided in the first and second aspects of the invention are provided for use in the fields of motor vehicle exhaust purification, industrial organic waste gas treatment, natural gas catalytic combustion, petrochemicals, hydrogen energy, and batteries.

[0033] In summary, this invention provides a grain boundary and surface-supported noble metal catalyst, its preparation method, and its application. In the catalyst, noble metal G is dispersed at the grain boundaries and surfaces of alumina and / or rare earth manganese-zirconium composite oxides, forming a multiphase interface. This achieves the following beneficial technical effects: First, the multiphase interface has greater steric hindrance and stronger anchoring effect, which can inhibit the high-temperature migration, aggregation, and growth of noble metals, improve the high-temperature stability and catalytic performance of noble metals, and reduce the amount of noble metal used. Second, the multiphase interface has a synergistic catalytic effect, which can reduce the lattice oxygen activation energy and increase the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity. Attached Figure Description

[0034] Figure 1 This is a flowchart illustrating the preparation method of noble metal catalysts supported on grain boundaries and surfaces, as described in this embodiment of the invention.

[0035] Figure 2 This is a flowchart of the preparation method of the honeycomb noble metal catalyst according to an embodiment of the present invention. Detailed Implementation

[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments and the accompanying drawings. It should be understood that these descriptions are merely exemplary and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.

[0037] This invention provides a grain boundary and surface-supported noble metal catalyst, comprising noble metal G, alumina, and / or rare earth manganese zirconium composite oxide, wherein the noble metal G is dispersed at the grain boundaries and surface of the alumina and / or rare earth manganese zirconium composite oxide, and the rare earth manganese zirconium composite oxide has the general chemical formula RE. a Mn b Zr c M d O (2-δ) D β ;in,

[0038] RE represents rare earth elements, M represents cationic dopant elements, and D represents anionic dopant elements.

[0039] 0.1≤a≤0.5, 0.05≤b≤0.3, 0.2≤c≤0.8, 0≤d≤0.2, 0≤δ≤0.1, 0≤β≤0.1, a+b+c+d=1.

[0040] This invention also provides a honeycomb noble metal catalyst, the catalyst comprising a honeycomb support, a noble metal G, and an active coating, wherein the active coating contains alumina and / or rare earth manganese zirconium composite oxide RE. a Mn b Zr c M d O (2-δ) D β The noble metal G is dispersed at the grain boundaries and surface of the active coating; wherein,

[0041] RE represents rare earth elements, M represents cationic dopant elements, and D represents anionic dopant elements.

[0042] 0.1≤a≤0.5, 0.05≤b≤0.3, 0.2≤c≤0.8, 0≤d≤0.2, 0≤δ≤0.1, 0≤β≤0.1, a+b+c+d=1.

[0043] The noble metal G can be one or more of Pt, Pd, Rh, Ir, Os, Ru, Au, and Ag, preferably one or more of Pt, Pd, Rh, and Ru, and more preferably a combination of Pt and Pd. The molar percentage of the noble metal G at the grain boundaries is 10-70 mol%. The noble metal G at the grain boundaries or surface is in a metallic state, or a combination of metallic and oxidized states; preferably, conversion to a metallic state is more beneficial to the catalytic effect. In this grain boundary and surface-supported noble metal catalyst, the loading of noble metal G, by mass percentage, is 0.01%-2%, preferably 0.1%-1%, and more preferably 0.1%-0.5%. In this honeycomb noble metal catalyst, the loading of noble metal G is 0.03-2.0 g / L, preferably 0.15-1.5 g / L. The total mass percentage of rare earth manganese zirconium composite oxide in the active coating is 0-100%, preferably 30-70%.

[0044] The grain boundary and surface-supported noble metal catalysts and honeycomb noble metal catalysts provided in this invention contain noble metal G at the grain boundaries and surfaces of rare earth manganese zirconium composite oxides and / or alumina, forming a multiphase interface. This multiphase interface has greater steric hindrance and stronger anchoring effect, which can inhibit the high-temperature migration, agglomeration and growth of noble metals, improve the high-temperature stability of noble metals, and reduce the amount of noble metals used. Furthermore, this multiphase interface has a synergistic catalytic effect, which can reduce the lattice oxygen activation energy and increase the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity.

[0045] In the rare earth manganese-zirconium composite oxide, the rare earth element RE includes one or more combinations of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc; preferably, one or more combinations of La, Ce, Pr, Nd, Sm, Eu, Gd, Yb, and Y. The doping element M is one or more combinations of transition metal elements, alkaline earth metal elements, and Al, Si, and Sn; the doping element D includes one or more combinations of anions N, P, and F.

[0046] In the rare earth manganese zirconium composite oxide, the transition metal element is one or more of Fe, Co, Ni, Cu, Zn, Ti, Hf, V, Cr, Nb, Mo and W, preferably one or more of Fe, Co, Ni, Cu and Hf; the alkaline earth metal element is one or more of Mg, Ca, Sr and Ba, preferably one or more of Sr and Ba.

[0047] This invention also provides a method for preparing grain boundary and surface-supported noble metal catalysts to prepare the grain boundary and surface-supported noble metal catalysts provided in the above embodiments. The flowchart of this method is as follows: Figure 1 As shown, it includes the following steps:

[0048] S1. Mix rare earth manganese zirconium composite oxide and / or alumina with the liquid salt of noble metal G evenly and then dry; the liquid salt of noble metal G can be one or more of the following: molten salt or aqueous solution of chloride, nitrate, acetate and citrate. The drying temperature is 50-200℃ and the time is 1h-48h.

[0049] S2. The wet composite compound obtained in step S1 is subjected to one or two heat treatments at a temperature of 200-750℃ for a time of 0.5-24 hours; preferably, the heat treatment temperature is 400-700℃ for a time of 1-12 hours. To meet the specific requirements of different applications for the performance of noble metal catalysts loaded at grain boundaries and on the surface, it is necessary to adjust or change the microstructure of the catalyst, thus requiring different heat treatment regimes, such as step-by-step heat treatment, to allow more noble metal to enter the grain boundaries more uniformly and stably. Water washing or water quenching can also be performed between the two heat treatment steps.

[0050] S3. The product obtained in step S2 is calcined once or twice in air or a reducing atmosphere to obtain a rare earth manganese zirconium composite oxide and / or alumina grain boundary and surface-supported noble metal catalyst. The loading of noble metal G in the catalyst is 0.01%-2% by mass, preferably 0.1%-1%. The reducing atmosphere includes one or more combinations of CO and H2. The calcination temperature is 400-850℃, and the time is 0.5h-24h; preferably, the calcination temperature is 450-750℃, and the time is 1h-12h. The grain boundary and surface-supported noble metal catalyst obtained above, after 1-2 calcinations, yields a catalyst material with a specific structure. After the first calcination, surface treatment can be performed to avoid secondary sintering and agglomeration.

[0051] In the above embodiment, during heat treatment in step S2, by controlling an appropriate temperature, the grain boundaries of rare earth manganese zirconium composite oxide and / or alumina begin to activate, thus becoming channels for noble metal diffusion. By controlling the heat treatment time, the depth and distribution of noble metal diffusion along the grain boundaries can be controlled. In step S3, by controlling the air or reducing atmosphere, reduction temperature, and reduction time, the noble metal at the grain boundaries and surface can be reduced or partially reduced. Through steps S2 and S3, the noble metal is distributed at the grain boundaries and surface of rare earth manganese zirconium composite oxide and / or alumina, forming a multiphase interface. This multiphase interface has greater steric hindrance and stronger anchoring effect, which can inhibit the high-temperature migration, agglomeration, and growth of noble metal, improve the high-temperature stability of noble metal, and reduce the amount of noble metal used. Furthermore, this multiphase interface has a synergistic catalytic effect, which can reduce the lattice oxygen activation energy and increase the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity.

[0052] This invention also provides a method for preparing a honeycomb-type noble metal catalyst, wherein the honeycomb-type noble metal catalyst provided in the above embodiments is coated with one or more coating materials in layers or sections. The coating material is one or two of the following: alumina, rare earth manganese zirconium composite oxide, alumina with noble metals loaded at grain boundaries and on the surface, rare earth manganese zirconium composite oxide with noble metals loaded at grain boundaries and on the surface, and a mixture of rare earth manganese zirconium composite oxide with noble metals loaded at grain boundaries and on the surface and alumina. The flowchart of this method is shown below. Figure 2 As shown, it includes the following steps:

[0053] A1. The coating material is mixed evenly with adhesive, acidity regulator and water through one or more steps to prepare a coating slurry;

[0054] A2. Apply the coating slurry obtained in step A1 onto the honeycomb carrier in one or more steps, or in sections or layers, and then dry it. The honeycomb carrier can be porous ceramic or metal. The drying temperature is 50-200℃, and the time is 1h-48h.

[0055] A3. The product obtained in step A2 is heat-treated and / or calcined in air or a reducing atmosphere to obtain a honeycomb-type noble metal catalyst. The loading of noble metal G in the catalyst is 0.03-2.0 g / L, preferably 0.15-1.5 g / L. The heat treatment temperature is 200-750℃, and the time is 0.5h-24h; preferably, the heat treatment temperature is 400-700℃, and the heat treatment time is 1h-12h. To meet the special requirements of different applications for the performance of the honeycomb-type noble metal catalyst, it is necessary to adjust or change the microstructure of the catalyst, thus requiring different heat treatment regimes, such as stepwise heat treatment, to allow more and more uniform and stable noble metal to enter the grain boundaries. Water washing, water quenching, etc., can also be performed between the two heat treatment steps. The calcination temperature is 400-850℃, and the time is 0.5h-24h; preferably, the calcination temperature is 450-750℃, and the time is 1h-12h. The honeycomb-type noble metal catalyst obtained above can be calcined 1-2 times to obtain a catalyst with a specific structure. After the first calcination, surface treatment can be performed to avoid secondary sintering and agglomeration.

[0056] This invention also provides a method for preparing a honeycomb-type noble metal catalyst. To prepare the honeycomb-type noble metal catalyst provided in the above embodiments, rare earth manganese zirconium composite oxide and / or alumina, noble metal G liquid salt, acidity regulator, binder and water are mixed uniformly in one or more steps to prepare a coating slurry. The slurry is coated onto a honeycomb support in one or more steps, or coated onto the honeycomb support in sections or layers, and then dried. The dried honeycomb support is then heat-treated and / or calcined under a reducing atmosphere to obtain the honeycomb-type noble metal catalyst.

[0057] This invention provides a grain boundary and surface-supported noble metal catalyst and a honeycomb noble metal catalyst, respectively. The noble metal is dispersed at the grain boundaries and surface of alumina and / or rare earth manganese zirconium composite oxides to form a multiphase interface. This multiphase interface has greater steric hindrance and stronger anchoring effect, which can inhibit the high-temperature migration, agglomeration and growth of noble metals, improve the high-temperature stability and catalytic performance of noble metals, and reduce the amount of noble metals used. Furthermore, this multiphase interface has a synergistic catalytic effect, which can reduce the lattice oxygen activation energy and increase the amount of active oxygen, thereby improving the low-temperature catalytic activity of NO oxidation.

[0058] This invention also provides applications of the above-mentioned grain boundary and surface-supported noble metal catalysts and honeycomb noble metal catalysts in the fields of motor vehicle exhaust purification, industrial waste gas treatment, natural gas catalytic combustion, petrochemicals, hydrogen energy, and batteries. The grain boundary and surface-supported noble metal catalysts and honeycomb noble metal catalysts provided in this invention exhibit excellent low-temperature catalytic activity and high-temperature stability for NO oxidation, meeting the application requirements of various related fields.

[0059] The present invention will be further described below through specific embodiments.

[0060] Comparative Example 1:

[0061] A certain volume of liquid platinum nitrate was measured with a Pt loading of 0.2 wt%, and then reacted with rare earth manganese zirconium composite oxide Ce. 0.10 Mn 0.05 Y 0.05 Zr 0.80 The solid O2 powder was mixed evenly, then dried at 120°C for 10 h, and then calcined at 700°C for 3 h in air atmosphere to obtain the catalyst Pt (0.2 wt%) / Ce. 0.10 Mn 0.05 Y 0.05 Zr 0.80 O2. The catalytic performance of the above catalysts was tested. The maximum NO conversion rate was 63.52%, and the temperature corresponding to the maximum NO conversion rate was 326℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 49.38%.

[0062] Comparative Example 2:

[0063] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.2 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.05 Pr 0.05 Zr 0.70 O 1.99 The solid powders were mixed evenly, then dried at 100°C for 6 hours, and subsequently calcined at 600°C for 6 hours in air atmosphere to obtain the catalyst Pt (0.2 wt%) / Ce. 0.20 Mn 0.05 Pr 0.05 Zr 0.70 O 1.99 The catalysts were subjected to catalytic performance tests. The maximum NO conversion rate was 64.06%, and the temperature corresponding to the maximum NO conversion rate was 324℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 50.37%.

[0064] Comparative Example 3:

[0065] A certain volume of liquid platinum nitrate salt was measured according to the loading of Pt (1.1 g / L), and then Al2O3 and Ce were added. 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.99Acidity regulator, water, and liquid platinum nitrate salt were uniformly mixed, and then a binder was added and mixed evenly to form a slurry. This slurry was then coated onto a cordierite ceramic honeycomb carrier, dried at 80°C for 8 hours, and calcined at 600°C for 3 hours under a H2 reducing atmosphere to obtain a honeycomb noble metal catalyst Pt (1.1 g / L) / Ce. 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.3 0O 1.99 -Al2O3. The catalytic performance of the above catalyst was tested. The maximum NO conversion rate was 65.54%, and the temperature corresponding to the maximum NO conversion rate was 330℃. After hydrothermal aging at 650℃ / 10%H2O / 100h, the maximum NO conversion rate of the catalyst was 50.93%.

[0066] Example 1:

[0067] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.2 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.10 Mn 0.05 Y 0.05 Zr 0.80 The solid O2 powder was mixed evenly, then dried at 120℃ for 10 h, heat-treated at 500℃ for 3 h, and calcined at 700℃ for 3 h under a H2 reducing atmosphere to obtain the catalyst Pt (0.2 wt%) / Ce. 0.10 Mn 0.05 Y 0.05 Zr 0.80 O2. Precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese-zirconium composite oxide. Catalytic performance tests were conducted on the above catalyst. The maximum NO conversion rate was 71.44%, and the temperature corresponding to the maximum NO conversion rate was 283℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 60.13%.

[0068] Example 2:

[0069] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.2 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.05 Pr 0.05 Zr 0.70 O 1.99 The solid powders were mixed evenly, dried at 100℃ for 6 hours, then heat-treated at 200℃ for 6 hours, heat-treated at 500℃ for 2 hours, and calcined at 600℃ for 6 hours under a H2 reducing atmosphere to obtain the catalyst Pt (0.2wt%) / Ce. 0.20 Mn 0.05 Pr 0.05 Zr0.70 O 1.99 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 75.52%, and the temperature corresponding to the maximum NO conversion rate was 273℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 65.31%.

[0070] Example 3:

[0071] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.2 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.10 Yb 0.10 Zr 0.60 O 1.99 The solid powders were mixed evenly, dried at 110℃ for 12 hours, then heat-treated at 530℃ for 3 hours, and calcined at 650℃ for 3 hours under a H2 reducing atmosphere to obtain the catalyst Pt (0.2wt%) / Ce. 0.20 Mn 0.10 Yb 0.10 Zr 0.60 O 1.99 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 73.54%, and the temperature corresponding to the maximum NO conversion rate was 277℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst remained at 63.54%.

[0072] Example 4:

[0073] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.2 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.10 Gd 0.20 Zr 0.50 O 1.99 The solid powders were mixed evenly, dried at 90℃ for 23 hours, then heat-treated at 530℃ for 3 hours, and calcined at 650℃ for 3 hours to obtain the catalyst Pt (0.2wt%) / Ce. 0.20 Mn 0.10 Gd 0.20 Zr 0.50 O 1.99 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 74.78%, and the temperature corresponding to the maximum NO conversion rate was 273℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 64.43%.

[0074] Example 5:

[0075] A certain volume of chloroplatinic acid solution with a Pt loading of 0.3 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.15 Eu 0.15 Zr 0.50 O 1.99 The solid powders were mixed evenly, washed, dried at 100℃ for 13 hours, then heat-treated at 530℃ for 3 hours, and calcined at 650℃ for 3 hours under a H2 reducing atmosphere to obtain the catalyst Pt (0.3wt%) / Ce. 0.20 Mn 0.15 Eu 0.15 Zr 0.50 O 1.99 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 76.63%, and the temperature corresponding to the maximum NO conversion rate was 267℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 65.16%.

[0076] Example 6:

[0077] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.4 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.15 Nd 0.15 Zr 0.50 O 1.99 The solid powders were mixed evenly, dried at 110℃ for 15 h, then heat-treated at 550℃ for 2 h, and calcined at 650℃ for 5 h under a H2 reducing atmosphere to obtain the catalyst Pt (0.4 wt%) / Ce. 0.20 Mn 0.15 Nd 0.15 Zr 0.50 O 1.99 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 77.34%, and the temperature corresponding to the maximum NO conversion rate was 266℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 66.68%.

[0078] Example 7:

[0079] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.4 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.15 La 0.15 Zr 0.50 O1.99 The solid powders were mixed evenly, dried at 90℃ for 10 h, then heat-treated at 550℃ for 2 h, and calcined at 650℃ for 5 h under a H2 reducing atmosphere to obtain the catalyst Pt (0.4 wt%) / Ce. 0.20 Mn 0.15 La 0.15 Zr 0.50 O 1.99 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 76.91%, and the temperature corresponding to the maximum NO conversion rate was 267℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 65.33%.

[0080] Example 8:

[0081] A certain volume of liquid palladium nitrate salt with a Pd loading of 0.4 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The solid powders were mixed evenly, dried at 100℃ for 24 hours, then heat-treated at 550℃ for 2 hours, and calcined at 650℃ for 5 hours under a H2 reducing atmosphere to obtain the catalyst Pd (0.4wt%) / Ce. 0.20 Mn 0.2 0La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The precious metal Pd is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 74.74%, and the temperature corresponding to the maximum NO conversion rate was 270℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 63.16%.

[0082] Example 9:

[0083] A certain volume of liquid platinum acetate was measured with a Pt loading of 0.4 wt%, and then reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02The solid powders were mixed evenly, dried at 90℃ for 20 h, then heat-treated at 550℃ for 6 h, and calcined at 650℃ for 5 h under a H2 reducing atmosphere to obtain the catalyst Pt (0.4 wt%) / Ce. 0.20 Mn 0.2 0La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 77.78%, and the temperature corresponding to the maximum NO conversion rate was 266℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 64.37%.

[0084] Example 10:

[0085] Based on 0.4 wt% Pt 0.5 Pd 0.5 A certain volume of liquid salts of platinum nitrate and palladium nitrate was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.90 N 0.10 The solid powders were mixed evenly, dried at 100℃ for 12 hours, then heat-treated at 450℃ for 6 hours, and calcined at 600℃ for 6 hours under a H2 reducing atmosphere to obtain the catalyst Pt. 0.5 Pd 0.5 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.90 N 0.10 Noble metals Pt and Pd are dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 78.13%, and the temperature corresponding to the maximum NO conversion rate was 261℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 68.49%.

[0086] Example 11:

[0087] Based on 0.4 wt% Pt 0.67 Pd 0.33 The alloy loading involves measuring a certain volume of liquid salts of platinum nitrate and palladium nitrate, and reacting them with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.20 La0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The solid powders were mixed evenly, dried at 100℃ for 20 h, then heat-treated at 450℃ for 6 h, and calcined at 600℃ for 8 h under a H2 reducing atmosphere to obtain the catalyst Pt. 0.67 Pd 0.33 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 Noble metals Pt and Pd are dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 80.30%, and the temperature corresponding to the maximum NO conversion rate was 242℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 73.11%.

[0088] Example 12:

[0089] Based on 0.4 wt% Pt 0.75 Pd 0.25 A certain volume of liquid salts of platinum nitrate and palladium nitrate was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.20 La 0.05 Nd 0.05 Zr 0.50 O 1.98 P 0.02 The solid powders were mixed evenly, dried at 90℃ for 24 hours, then heat-treated at 450℃ for 6 hours, and calcined at 600℃ for 8 hours under a H2 reducing atmosphere to obtain the catalyst Pt. 0.75 Pd 0.25 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Nd 0.05 Zr 0.50 O 1.98 P 0.02 Noble metals Pt and Pd are dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 79.38%, and the temperature corresponding to the maximum NO conversion rate was 253℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 70.16%.

[0090] Example 13:

[0091] Based on 0.4 wt% Pt 0.91 Pd 0.09 The alloy loading involves measuring a certain volume of liquid salts of platinum nitrate and palladium nitrate, and reacting them with rare earth manganese zirconium composite oxide Ce. 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr 0.58 The solid O2 powder was mixed evenly, dried at 120℃ for 6 hours, then heat-treated at 450℃ for 6 hours, and calcined at 600℃ for 8 hours under a H2 reducing atmosphere to obtain the catalyst Pt. 0.91 Pd 0.09 (0.4wt%) / Ce 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr 0.58 O2. Noble metals Pt and Pd are dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalyst. The maximum NO conversion rate was 80.63%, and the temperature corresponding to the maximum NO conversion rate was 241℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 74.36%.

[0092] Example 14:

[0093] Based on 0.4 wt% Pt 0.83 Pd 0.17 The alloy loading involves measuring a certain volume of liquid salts of platinum nitrate and palladium nitrate, and reacting them with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 F 0.02 The solid powders were mixed evenly, dried at 80℃ for 24 hours, then heat-treated at 450℃ for 6 hours, and calcined at 600℃ for 8 hours under a H2 reducing atmosphere to obtain the catalyst Pt. 0.83 Pd 0.17 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 F 0.02Noble metals Pt and Pd are dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 79.43%, and the temperature corresponding to the maximum NO conversion rate was 246℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 71.67%.

[0094] Example 15:

[0095] Based on 0.4 wt% Pt 0.91 Pd 0.09 A certain volume of liquid salts of platinum nitrate and palladium nitrate was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.20 La 0.02 Nd 0.03 Y 0.03 Cu 0.02 Zr 0.50 O 1.98 The solid powder was mixed evenly, dried at 150℃ for 10 h, then heat-treated at 450℃ for 6 h, and calcined at 600℃ for 8 h under a H2 reducing atmosphere to obtain the catalyst Pt. 0.91 Pd 0.09 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.02 Nd 0.03 Y 0.03 Cu 0.02 Zr 0.50 O 1.98 Noble metals Pt and Pd are dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 82.39%, and the temperature corresponding to the maximum NO conversion rate was 236℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 76.88%.

[0096] Example 16:

[0097] Take a certain amount of Pt prepared in Example 15 0.91 Pd 0.09 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.02 Nd 0.03 Y 0.03 Cu 0.02 Zr 0.50 O 1.98The catalyst was then mixed with a binder, acidity regulator, and water to form a slurry, which was then coated onto a cordierite ceramic honeycomb carrier. The slurry was dried at 100°C for 4 hours, followed by calcination at 550°C in air for 5 hours to obtain the honeycomb-type noble metal catalyst Pt. 0.91 Pd 0.09 (0.35g / L) / Ce 0.20 Mn 0.20 La 0.02 Nd 0.03 Y 0.03 Cu 0.02 Zr 0.50 O 1.99 The noble metals Pt and Pd are dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 83.86%, and the temperature corresponding to the maximum NO conversion rate was 230℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 75.1%.

[0098] Example 17:

[0099] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.6 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.20 La 0.02 Nd 0.03 Sm 0.03 Y 0.02 Zr 0.50 O 1.98 The solid powders were mixed evenly, dried at 60℃ for 32 hours, then heat-treated at 400℃ for 9 hours, and calcined at 550℃ for 9 hours under a H2 reducing atmosphere to obtain the catalyst Pt (0.6wt%) / Ce. 0.20 Mn 0.20 La 0.02 Nd 0.03 Sm 0.03 Y 0.02 Zr 0.50 O 1.98 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 80.36%, and the temperature corresponding to the maximum NO conversion rate was 245℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 70.43%.

[0100] Example 18:

[0101] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.8 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.20 Mn 0.30 La0.02 Co 0.03 Y 0.05 Zr 0.40 O 1.98 The solid powders were mixed evenly, dried at 100℃ for 6 hours, then heat-treated at 400℃ for 9 hours, and calcined at 550℃ for 12 hours under a H2 reducing atmosphere to obtain the catalyst Pt (0.8wt%) / Ce. 0.20 Mn 0.30 La 0.02 Co 0.03 Y 0.05 Zr 0.40 O 1.98 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 78.36%, and the temperature corresponding to the maximum NO conversion rate was 246℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 68.41%.

[0102] Example 19:

[0103] A certain volume of ruthenium nitrate liquid salt with a Ru loading of 0.1 wt% was measured and reacted with rare earth manganese zirconium composite oxide Ce. 0.40 Mn 0.05 La 0.05 Sr 0.05 Sc 0.05 Zr 0.40 O 1.98 The solid powders were mixed evenly, dried at 80℃ for 30 h, then heat-treated at 700℃ for 1 h, and calcined at 750℃ for 9 h under a CO reducing atmosphere to obtain the catalyst Ru (0.1 wt%) / Ce. 0.40 Mn 0.0 5La 0.05 Sr 0.05 Sc 0.05 Zr 0.40 O 1.98 The precious metal Ru is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 69.16%, and the temperature corresponding to the maximum NO conversion rate was 276℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 59.38%.

[0104] Example 20:

[0105] A certain volume of liquid iridium nitrate was measured with an Ir loading of 0.1 wt%, and then reacted with Ce. 0.40 Mn 0.05 La 0.05 Ba 0.05 Al0.05 Zr 0.40 O 1.98 The solid powder was mixed evenly, dried at 120℃ for 5 hours, then heat-treated at 600℃ for 9 hours, and calcined at 750℃ for 6 hours under a H2 reducing atmosphere to obtain the catalyst Ir (0.1wt%) / Ce. 0.40 Mn 0.05 La 0.05 Ba 0.05 Al 0.05 Zr 0.4 0O 1.98 The precious metal Ir is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 68.11%, and the temperature corresponding to the maximum NO conversion rate was 279℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 56.9%.

[0106] Example 21:

[0107] A certain volume of osmium acetate liquid salt was measured with an Os loading of 0.01 wt%, and then mixed with Ce. 0.40 Mn 0.05 La 0.05 Hf 0.05 Ni 0.05 Zr 0.40 O 1.98 The solid powder was mixed evenly, dried at 160℃ for 1 hour, then heat-treated at 750℃ for 0.5 hours, and calcined at 800℃ for 1 hour under a H2 reducing atmosphere to obtain the catalyst Os (0.01wt%) / Ce. 0.40 Mn 0.05 La 0.05 Hf 0.05 Ni 0.05 Zr 0.40 O 1.98 The noble metal Os is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 66.39%, and the temperature corresponding to the maximum NO conversion rate was 286℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 53.83%.

[0108] Example 22:

[0109] A certain volume of liquid platinum nitrate was measured with a Pt loading of 0.8 wt%, and mixed with 30 g of Ce. 0.20 Mn 0.30 La 0.05 Y 0.0 5Zr 0.40 O 1.98The mixture was thoroughly mixed with 70g of solid alumina powder, dried at 90℃ for 6h, then heat-treated at 400℃ for 9h, and calcined at 550℃ for 9h under a H2 reducing atmosphere to obtain the catalyst Pt (0.8wt%) / Ce. 0.20 Mn 0.30 La 0.05 Y 0.05 Zr 0.4 0O 1.98 -Al2O3. Noble metal Pt is dispersed at the grain boundaries and surface of rare earth manganese zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 79.93%, corresponding to a temperature of 243℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 70.53%.

[0110] Example 23:

[0111] A certain amount of Pt (0.8 wt%) / Ce prepared in Example 22 was taken. 0.20 Mn 0.30 La 0.05 Y 0.05 Zr 0.40 O 1.98 Al2O3 catalyst was mixed with binder, acidity regulator, water, etc. to form a slurry, which was then coated onto a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 100°C for 4 hours and calcined at 600°C for 1 hour in air to obtain a honeycomb noble metal catalyst Pt(0.5 g / L) / Ce. 0.20 Mn 0.30 La 0.05 Y 0.05 Zr 0.40 O 1.98 Al₂O₃ and precious metal Pt are dispersed at the grain boundaries and surfaces of rare earth manganese-zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 81.69%, corresponding to a temperature of 241℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate of the catalyst was 73.18%.

[0112] Example 24:

[0113] A certain volume of liquid platinum nitrate was measured with a Pt loading of 1.0 wt%, and mixed with 40 g of Ce. 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.98The mixture was thoroughly mixed with 60g of solid alumina powder, dried at 130℃ for 2h, then heat-treated at 450℃ for 12h, and calcined at 700℃ for 7h under a H2 reducing atmosphere to obtain the catalyst Pt (1.0wt%) / Ce. 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.98 -Al2O3. Noble metal Pt is dispersed at the grain boundaries and surfaces of rare earth manganese zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 78.61%, corresponding to a temperature of 253℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 66.84%.

[0114] Example 25:

[0115] A certain volume of liquid platinum nitrate was measured with a Pt loading of 1.0 wt%, and mixed with 50 g of Ce. 0.30 Mn 0.30 La 0.05 Cu 0.05 Zr 0.30 O 1.98 The mixture was thoroughly mixed with 50g of solid alumina powder, dried at 140℃ for 5h, then heat-treated at 450℃ for 12h, and calcined at 700℃ for 8h under a H2 reducing atmosphere to obtain the catalyst Pt (1.0wt%) / Ce. 0.30 Mn 0.30 La 0.05 Cu 0.05 Zr 0.30 O 1.98 -Al2O3. Noble metal Pt is dispersed at the grain boundaries and surfaces of rare earth manganese-zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 77.36%, corresponding to a temperature of 256℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 65.18%.

[0116] Example 26:

[0117] A certain volume of liquid platinum nitrate was measured with a Pt loading of 1.0 wt%, and mixed with 60 g of Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 Ti 0.20 Zr 0.20 O 1.98The mixture was thoroughly mixed with 40g of solid alumina powder, dried at 80℃ for 9h, then heat-treated at 450℃ for 12h, and calcined at 700℃ for 7h under a reducing atmosphere of H2 to obtain the catalyst Pt (1.0wt%) / Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 Ti 0.20 Zr 0.20 O 1.98 -Al2O3. Noble metal Pt is dispersed at the grain boundaries and surfaces of rare earth manganese zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 77.7%, corresponding to a temperature of 272℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 66.79%.

[0118] Example 27:

[0119] A certain volume of liquid platinum nitrate was measured with a Pt loading of 2.0 wt%, and mixed with 70 g of Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 The mixture was thoroughly mixed with 30g of solid alumina powder, dried at 200℃ for 1h, then heat-treated at 600℃ for 6h, and calcined at 700℃ for 9h under a reducing atmosphere of H2 to obtain the catalyst Pt (2.0wt%) / Ce. 0.40 Mn 0.10 La 0.0 5Nd 0.05 V 0.20 Zr 0.20 O 1.98 -Al2O3. Noble metal Pt is dispersed at the grain boundaries and surfaces of rare earth manganese-zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 78.6%, corresponding to a temperature of 269℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 67.46%.

[0120] Example 28:

[0121] A certain volume of liquid rhodium nitrate was measured with a 0.5 wt% Rh loading and mixed with 80 g of Ce. 0.40 Mn 0.05 La 0.05 Nd 0.05 Nb 0.05 Zr 0.40 O 1.98The mixture was thoroughly mixed with 20g of solid alumina powder, dried at 50℃ for 48h, then heat-treated at 300℃ for 3h, and calcined at 850℃ for 0.5h under a H2 reducing atmosphere to obtain catalyst Rh (0.5wt%) / Ce. 0.40 Mn 0.05 La 0.05 Nd 0.05 Nb 0.05 Zr 0.40 O 1.98 -Al2O3. The noble metal Rh is dispersed at the grain boundaries and surface of the rare earth manganese-zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 73.43%, corresponding to a temperature of 269℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 61.53%.

[0122] Example 29:

[0123] A certain volume of liquid silver citrate was measured with an Ag loading of 0.5 wt%, and mixed with 90 g of Ce. 0.40 Mn 0.05 La 0.05 Nd 0.05 Si 0.05 Zr 0.40 O 1.98 The mixture was thoroughly mixed with 10g of solid alumina powder, dried at 160℃ for 4 hours, then heat-treated at 600℃ for 9 hours, and calcined at 750℃ for 6 hours under a H2 reducing atmosphere to obtain the catalyst Ag(0.5wt%) / Ce. 0.40 Mn 0.05 La 0.0 5Nd 0.05 Si 0.05 Zr 0.40 O 1.98 -Al2O3. Noble metal Ag is dispersed at the grain boundaries and surfaces of rare earth manganese-zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 70.93%, corresponding to a temperature of 270℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 60.37%.

[0124] Example 30:

[0125] A certain volume of liquid chloroauric acid salt with an Au loading of 0.5 wt% was measured and mixed with 90 g of Ce. 0.40 Mn 0.05 La 0.05 Nd 0.05 Fe 0.05 Zr 0.40 O 1.98The mixture was thoroughly mixed with 10g of solid alumina powder, washed, dried at 100℃ for 8 hours, then heat-treated at 200℃ for 24 hours, and calcined at 400℃ for 24 hours under a H2 reducing atmosphere to obtain the catalyst Au(0.5wt%) / Ce. 0.40 Mn 0.05 La 0.05 Nd 0.05 Fe 0.05 Zr 0.40 O 1.98 -Al2O3. The noble metal Au is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 71.34%, and the temperature corresponding to the maximum NO conversion rate was 281℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 60.66%.

[0126] Example 31:

[0127] A certain volume of liquid platinum nitrate salt with a Pt loading of 1.0 wt% was measured and mixed evenly with solid alumina powder. The mixture was dried at 50℃ for 6 h, then heat-treated at 450℃ for 12 h, and calcined at 700℃ for 7 h under a H2 reducing atmosphere to obtain the catalyst Pt(1.0 wt%) / Al2O3. The noble metal Pt is dispersed at the grain boundaries and surface of the alumina. Catalytic performance tests were conducted on the catalyst. The maximum NO conversion rate was 70.96%, and the temperature corresponding to the maximum NO conversion rate was 283℃. After hydrothermal aging at 650℃ / 10% H2O / 100 h, the maximum NO conversion rate of the catalyst was 60.31%.

[0128] Example 32:

[0129] A certain amount of the Pt (1.0 wt%) / Al2O3 catalyst prepared in Example 31 was taken, and then a binder, acidity regulator, water, etc. were added and mixed evenly to form a slurry. This slurry was then coated onto a cordierite ceramic honeycomb support and dried at 110°C for 5 hours. Subsequently, the honeycomb support was calcined in air at 450°C for 6 hours to obtain a honeycomb-type noble metal catalyst Pt (0.03 g / L) / Al2O3, in which the noble metal Pt was dispersed at the grain boundaries and surface of alumina. The catalyst was subjected to catalytic performance testing. The maximum NO conversion rate was 68.33%, and the temperature corresponding to the maximum NO conversion rate was 279°C. After hydrothermal aging at 650°C / 10% H2O / 100 hours, the maximum NO conversion rate of the catalyst was 60.93%.

[0130] Example 33:

[0131] A certain volume of liquid platinum nitrate salt with a Pt loading of 0.2 wt% was measured and reacted with Ce. 0.20 Mn 0.15Y 0.15 Zr 0.50 O 1.99 The solid powders were mixed evenly, dried at 110℃ for 12 hours, then heat-treated at 530℃ for 8 hours, and calcined at 650℃ for 3 hours under a H2 reducing atmosphere to obtain the catalyst Pt (0.2wt%) / Ce. 0.20 Mn 0.15 Y 0.15 Zr 0.50 O 1.99 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalyst. The maximum NO conversion rate was 76.49%, corresponding to a temperature of 270℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 63.31%.

[0132] Example 34:

[0133] A certain amount of Pt (0.2 wt%) / Ce prepared in Example 33 was taken. 0.20 Mn 0.15 Y 0.15 Zr 0.50 O 1.99 The catalyst was then mixed with binder, acidity regulator, water, etc., to form a slurry, which was then coated onto a cordierite ceramic honeycomb carrier. The slurry was dried at 130°C for 6 hours, followed by calcination at 500°C for 3 hours in air to obtain a honeycomb-type noble metal catalyst Pt(0.15 g / L) / Ce. 0.20 Mn 0.15 Y 0.15 Zr 0.50 O 1.99 The precious metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. Catalytic performance tests were conducted on the above catalyst. The maximum NO conversion rate was 76.43%, and the temperature corresponding to the maximum NO conversion rate was 266℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 65.13%.

[0134] Example 35:

[0135] A certain volume of liquid platinum nitrate salt was measured according to the loading of Pt (1.1 g / L), and Al2O3 and Ce were added. 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.99Acidity regulator, water, etc., are uniformly mixed, and then a binder is added and mixed evenly to form a slurry. This slurry is then coated onto a cordierite ceramic honeycomb carrier, dried at 80℃ for 8 hours, heat-treated at 400℃ for 8 hours, and calcined at 600℃ for 3 hours under a H2 reducing atmosphere to obtain a honeycomb noble metal catalyst Pt (1.1 g / L) / Ce. 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.99 Al2O3 and precious metal Pt are dispersed at the grain boundaries and surfaces of rare earth manganese zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 79.17%, corresponding to a temperature of 236℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 68.37%.

[0136] Example 36:

[0137] A certain volume of liquid platinum nitrate was measured according to the Pt (1.5 g / L) loading, and Al2O3, acidity regulator, water, etc. were added and mixed evenly. Then, a binder was added and mixed evenly to form a slurry, which was then coated onto a cordierite ceramic honeycomb carrier. The slurry was dried at 150℃ for 3 h, then heat-treated at 500℃ for 6 h, and calcined at 550℃ for 2 h under a H2 reducing atmosphere to obtain a honeycomb noble metal catalyst Pt (1.5 g / L) / Al2O3, with the noble metal Pt dispersed at the grain boundaries and surface of alumina. The catalyst was tested for catalytic performance. The maximum NO conversion rate was 72.36%, and the temperature corresponding to the maximum NO conversion rate was 266℃. After hydrothermal aging at 650℃ / 10% H2O / 100 h, the maximum NO conversion rate of the catalyst was 62.11%.

[0138] Example 37:

[0139] A certain volume of liquid platinum nitrate was measured according to the Pt (2.0 g / L) loading, and then mixed with Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98Acidity regulator, water, etc., are uniformly mixed, and then a binder is added and mixed evenly to form a slurry. This slurry is then coated onto a cordierite ceramic honeycomb carrier, dried at 100℃ for 4 hours, heat-treated at 380℃ for 7 hours, and calcined at 500℃ for 4 hours in a H2 reducing atmosphere. Then, Al2O3, binder, acidity regulator, water, etc., are mixed to form a slurry, coated onto the calcined cordierite ceramic honeycomb carrier, dried at 90℃ for 3 hours, and calcined at 450℃ for 8 hours to obtain a honeycomb-type noble metal catalyst Pt (2.0 g / L) / Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 Al₂O₃ and precious metal Pt are dispersed at the grain boundaries and surface of the rare earth manganese-zirconium composite oxide. Catalytic performance tests were conducted on the above catalyst. The maximum NO conversion rate was 81.19%, and the temperature corresponding to the maximum NO conversion rate was 239℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate of the catalyst was 70.19%.

[0140] Example 38:

[0141] A certain volume of liquid platinum nitrate was measured according to the Pt (1.3 g / L) loading, and uniformly mixed with Al2O3, acidity regulator, water, etc. Then, a binder was added and mixed evenly to form a slurry, which was then coated onto a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 120℃ for 4 hours, heat-treated at 430℃ for 5 hours, and calcined at 500℃ for 7 hours under a H2 reducing atmosphere. Finally, Ce... 0.30 Mn 0.30 La 0.05 Cu 0.05 Zr 0.30 O 1.98 A slurry was prepared by mixing binder, acidity regulator, water, etc., and coated onto the calcined cordierite ceramic honeycomb carrier. The slurry was then dried at 90°C for 3 hours, removed, and calcined again at 450°C in air for 2 hours to obtain the honeycomb noble metal catalyst Pt(1.3 g / L) / Ce. 0.30 Mn 0.30 La 0.05 Cu 0.05 Zr 0.30 O 1.98 Al₂O₃, with precious metal Pt dispersed at the grain boundaries and surface of alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 80.60%, corresponding to a temperature of 233℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate of the catalyst was 69.33%.

[0142] Example 39:

[0143] A certain volume of liquid platinum nitrate was measured according to a Pt loading of 2.0 g / L. Half of the liquid platinum nitrate was then mixed with an appropriate amount of Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 Acidity regulator, water, etc., are mixed evenly, and then a binder is added and mixed evenly to form a coating slurry. This slurry is then coated onto a cordierite ceramic honeycomb carrier, dried at 110℃ for 6 hours, heat-treated at 500℃ for 6 hours, and calcined at 700℃ for 3 hours under a H2 reducing atmosphere. The remaining half of the liquid platinum nitrate salt is then mixed evenly with an appropriate amount of Al2O3 powder, acidity regulator, water, etc., and then a binder is added and mixed evenly to form a coating slurry. This slurry is then coated onto the calcined cordierite ceramic honeycomb carrier, dried at 90℃ for 3 hours, heat-treated at 560℃ for 4 hours, and calcined at 500℃ for 7 hours under a H2 reducing atmosphere to obtain a honeycomb noble metal catalyst Pt (2.0 g / L) / Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 Al₂O₃ and precious metal Pt are dispersed at the grain boundaries and surfaces of rare earth manganese-zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 82.96%, corresponding to a temperature of 236℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate of the catalyst was 70.16%.

[0144] Example 40:

[0145] A certain volume of liquid platinum nitrate was measured according to the loading of Pt (1.0 g / L), and mixed with 20 g of Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 Pr 0.20 Zr 0.20 O 1.9870g of alumina, acidity regulator, and water were uniformly mixed, and then a binder was added and mixed evenly to form a slurry. This slurry was then coated onto a cordierite ceramic honeycomb carrier. The mixture was dried at 80℃ for 13 hours, heat-treated at 330℃ for 8 hours, and calcined at 550℃ for 4 hours under a H2 reducing atmosphere. Then, 10g of alumina was weighed and uniformly mixed with the binder, acidity regulator, and water to form a slurry. This slurry was then coated onto the calcined cordierite ceramic honeycomb carrier, dried at 90℃ for 3 hours, and calcined at 600℃ in air for 1 hour to obtain a honeycomb-type noble metal catalyst Pt(1.0g / L) / Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 Pr 0.20 Zr 0.20 O 1.98 Al₂O₃ and precious metal Pt are dispersed at the grain boundaries and surfaces of rare earth manganese-zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 79.31%, corresponding to a temperature of 256℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate of the catalyst was 68.69%.

[0146] Example 41:

[0147] Weigh 40g of Al2O3 and mix it evenly with acidity regulator, binder, and water to form a slurry. Coat the slurry onto a cordierite ceramic honeycomb carrier. Then, dry the coated honeycomb carrier at 120℃ for 4 hours and calcine it at 500℃ for 7 hours in air. Then, measure a certain volume of liquid platinum nitrate salt according to the Pt (1.4g / L) loading and mix it with 40g of Ce. 0.30 Mn 0.20 La 0.10 Cu 0.10 Zr 0.30 O 1.98 20g Al2O3, acidity regulator, water, etc. were mixed evenly, and then a binder was added and mixed evenly to form a slurry. This slurry was then coated onto the calcined cordierite ceramic honeycomb carrier. The slurry was dried at 90℃ for 3 hours, heat-treated at 430℃ for 5 hours, and calcined at 550℃ under a hydrogen atmosphere for 3 hours to obtain a honeycomb noble metal catalyst Pt (1.4g / L) / Ce. 0.30 Mn 0.20 La 0.10 Cu 0.10 Zr 0.30 O 1.98Al₂O₃ and precious metal Pt are dispersed at the grain boundaries and surfaces of rare earth manganese zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 79.33%, corresponding to a temperature of 238℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate of the catalyst was 68.16%.

[0148] Example 42:

[0149] A certain volume of liquid platinum nitrate was measured with a Pt loading of 1.0 wt%, and mixed with 40 g of Ce. 0.20 Mn 0.25 La 0.05 Y 0.0 5Fe 0.05 Zr 0.40 O 1.98 The solid powders were mixed evenly, dried at 80℃ for 9 hours, then heat-treated at 410℃ for 6 hours, and calcined at 560℃ for 7 hours under a H2 reducing atmosphere to obtain the catalyst Pt (1.0 wt%) / Ce. 0.20 Mn 0.25 La 0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.9 The above catalyst was uniformly mixed with acidity regulator, binder, water, etc., to form a slurry, which was then coated onto a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 130℃ for 1 hour and calcined at 400℃ for 6 hours in air. Next, 60g of alumina was weighed and uniformly mixed with binder, acidity regulator, water, etc., to form a slurry, which was then coated onto the calcined cordierite ceramic honeycomb carrier. The mixture was dried at 90℃ for 3 hours and calcined at 550℃ in air for 1 hour to obtain the honeycomb-type noble metal catalyst Pt(1.6g / L) / Ce. 0.20 Mn 0.25 La 0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.98 -Al2O3. Noble metal Pt is dispersed at the grain boundaries and surface of the rare earth manganese-zirconium composite oxide. The catalytic performance of the above honeycomb noble metal catalyst was tested. The maximum NO conversion rate was 78.53%, and the temperature corresponding to the maximum NO conversion rate was 249℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 69.83%.

[0150] Example 43:

[0151] A certain amount of Al2O3 was weighed and uniformly mixed with acidity regulator, binder, water, etc., to form a slurry. This slurry was then coated onto a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 140°C for 3 hours and calcined at 600°C for 8 hours in air. A certain amount of Pt (1.0 wt%) / Ce prepared in Example 42 was then taken. 0.20 Mn 0.25 La 0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.9 The catalyst was uniformly mixed with binder, acidity regulator, water, etc., to form a slurry, which was then coated onto the calcined cordierite ceramic honeycomb carrier. The slurry was dried at 90℃ for 3 hours and calcined at 330℃ for 6 hours to obtain the honeycomb-type noble metal catalyst Pt(1.0 g / L) / Ce. 0.20 Mn 0.25 La 0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.9 Al₂O₃ and precious metal Pt are dispersed at the grain boundaries and surface of the rare earth manganese-zirconium composite oxide. Catalytic performance tests were conducted on the above catalyst. The maximum NO conversion rate was 79.19%, and the temperature corresponding to the maximum NO conversion rate was 239℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate of the catalyst was 70.37%.

[0152] Example 44:

[0153] A certain volume of liquid platinum nitrate with a Pt loading of 0.7 wt% was measured and mixed evenly with solid alumina powder. The mixture was dried at 70°C for 11 h, then heat-treated at 460°C for 5 h, and calcined at 550°C for 9 h under a H2 reducing atmosphere to obtain the catalyst Pt(0.7 wt%) / Al2O3. This catalyst was then uniformly mixed with an acidity regulator, binder, water, etc., to form a slurry. This slurry was coated onto a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 130°C for 1 h and calcined at 400°C for 6 h in air. Finally, 60 g of Ce was weighed out. 0.20 Mn 0.20 La 0.05 Y 0.05 Zn 0.10 Zr 0.40 O 1.98 The mixture was then uniformly mixed with binder, acidity regulator, water, etc., to form a slurry, which was then coated onto the calcined cordierite ceramic honeycomb carrier. The slurry was dried at 80°C for 8 hours and calcined at 460°C in air for 6 hours to obtain the honeycomb-type noble metal catalyst Pt(1.0 g / L) / Ce. 0.20 Mn 0.20La 0.0 5Y 0.05 Zn 0.10 Zr 0.40 O 1.98 -Al2O3. Noble metal Pt is dispersed at the grain boundaries and surface of alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 76.10%, corresponding to a temperature of 266℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 67.83%.

[0154] Example 45:

[0155] A certain volume of liquid platinum nitrate was measured with a Pt loading of 0.7 g / L and reacted with Ce. 0.20 Mn 0.15 Y 0.10 Eu 0.05 Zr 0.5 0O 1.99 Solid powder, acidity regulator, water, etc., were uniformly mixed, and a binder was added to form a slurry. This slurry was then coated onto the first half of the cordierite ceramic honeycomb carrier and dried at 100℃ for 6 hours. Then, appropriate amounts of alumina, acidity regulator, binder, water, etc., were uniformly mixed to form a slurry, which was then coated onto the remaining second half of the cordierite ceramic honeycomb carrier. This slurry was dried at 150℃ for 2 hours and calcined at 610℃ for 5 hours to obtain the honeycomb-type noble metal catalyst Pt (0.7 g / L) / Ce. 0.20 Mn 0.15 Y 0.10 Eu 0.05 Zr 0.50 O 1.99 Al2O3 and precious metal Pt are dispersed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance of the above honeycomb-type precious metal catalyst was tested. The maximum NO conversion rate was 77.71%, and the temperature corresponding to the maximum NO conversion rate was 266℃. After hydrothermal aging at 650℃ / 10% H2O / 100h, the maximum NO conversion rate of the catalyst was 64.93%.

[0156] Example 46:

[0157] A certain volume of liquid platinum nitrate was added to a Pt loading of 1.5 g / L, mixed evenly with a certain amount of alumina, acidity regulator, and water, and then a binder was added to prepare a coating slurry. This slurry was then coated onto the first half of the cordierite ceramic honeycomb carrier, dried at 80℃ for 9 hours, heat-treated at 380℃ for 6 hours, and calcined at 610℃ for 6 hours under a H2 reducing atmosphere. Finally, a certain amount of Ce was weighed out. 0.40 Mn 0.10 La 0.05 Nd 0.05 W 0.20 Zr0.20 O 1.98 The mixture was then uniformly mixed with binder, acidity regulator, water, etc., to form a slurry, which was then coated onto the remaining cordierite ceramic honeycomb carrier. The slurry was dried at 150℃ for 3 hours and calcined at 460℃ for 3 hours to obtain the honeycomb-type noble metal catalyst Pt(1.5g / L) / Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 W 0.20 Zr 0.20 O 1.98 Al₂O₃, with precious metal Pt dispersed at the grain boundaries and surface of alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 81.79%, corresponding to a temperature of 246℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate of the catalyst was 71.51%.

[0158] Example 47:

[0159] A certain volume of liquid platinum nitrate was measured according to a Pt loading of 1.3 g / L. Half of this liquid platinum nitrate was then mixed with Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 Pr 0.20 Zr 0.20 O 1.98 Acidity regulator, water, etc., are mixed evenly, and then a binder is added and mixed evenly to form a coating slurry. This slurry is then coated onto the first half of the cordierite ceramic honeycomb carrier. The mixture is dried at 80℃ for 9 hours, heat-treated at 380℃ for 6 hours, and calcined at 610℃ for 6 hours under a H2 reducing atmosphere. The remaining half of the liquid platinum nitrate salt is then mixed evenly with alumina, acidity regulator, water, etc., and a binder is added and mixed evenly to form a slurry. This slurry is then coated onto the remaining second half of the cordierite ceramic honeycomb carrier. The mixture is dried at 150℃ for 3 hours, heat-treated at 460℃ for 6 hours, and calcined at 600℃ for 5 hours under a H2 reducing atmosphere to obtain the honeycomb noble metal catalyst Pt (1.3 g / L) / Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 Pr 0.20 Zr 0.20 O 1.98Al₂O₃ and precious metal Pt are dispersed at the grain boundaries and surfaces of rare earth manganese-zirconium composite oxide and alumina. Catalytic performance tests were conducted on the above catalysts. The maximum NO conversion rate was 80.16%, corresponding to a temperature of 251℃. After hydrothermal aging at 650℃ / 10% H₂O / 100h, the maximum NO conversion rate was 70.09%. The above testing process involved taking appropriate amounts of the precious metal catalyst loaded at grain boundaries and surfaces, as well as small samples of the honeycomb-type precious metal catalyst, for catalytic performance testing. Catalyst activity evaluation experiments were conducted in a microreactor, and the concentrations of NO, NO₂, and NO₃⁻ at corresponding temperatures were recorded using an infrared gas analyzer. x The content of the catalyst was used to calculate the maximum NO conversion rate and corresponding temperature of fresh samples, as well as the maximum NO conversion rate after aging at 650℃ / 10% H2O / 100h hydrothermal conditions. The catalytic test used a simulated automobile exhaust mixture with the following component contents (by volume): oxygen 8%, water 10%, carbon monoxide 500ppm, nitric oxide 500ppm, C3H6 200ppm, C3H8 100ppm; the balance gas was nitrogen. The reaction temperature was set to increase from room temperature to 400℃ at a rate of 20℃ / min for 20 min.

[0160] As the experimental results above show, the NO conversion rates of the grain boundary and surface-supported noble metal catalysts and honeycomb noble metal catalysts provided in the embodiments of this invention are significantly higher than those of the comparative catalyst samples, regardless of whether they are fresh or aged. Furthermore, the temperature corresponding to the maximum NO conversion rate of the fresh catalyst samples is also lower than that of the comparative catalyst samples. By diffusing noble metals to the grain boundaries and surfaces to form multiphase interfaces, the activation energy of lattice oxygen is reduced and the amount of active oxygen is increased, while the migration and growth of noble metal particles are prevented. Therefore, the grain boundary and surface-supported noble metal catalysts and honeycomb noble metal catalysts provided in the embodiments of this invention can significantly improve the low-temperature catalytic activity and high-temperature stability of NO oxidation.

[0161] In summary, this invention relates to a grain boundary and surface-supported noble metal catalyst, its preparation method, and its application. Noble metal G is uniformly dispersed at the grain boundaries and surfaces of alumina and / or rare earth manganese-zirconium composite oxides, forming a multiphase interface. This achieves the following beneficial technical effects: First, the multiphase interface has greater steric hindrance and stronger anchoring effect, which can inhibit the high-temperature migration, agglomeration, and growth of the noble metal, improve the high-temperature stability of the noble metal, and reduce the amount of noble metal used. Second, the multiphase interface has a synergistic catalytic effect, which can reduce the lattice oxygen activation energy and increase the amount of active oxygen, thereby improving the NO oxidation conversion rate and low-temperature catalytic activity.

[0162] It should be understood that the specific embodiments described above are merely illustrative or explanatory of the principles of the invention and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of the invention should be included within the protection scope of the invention. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the appended claims, or equivalent forms of such scope and boundaries.

Claims

1. A noble metal catalyst supported on grain boundaries and surfaces, characterized in that, The catalyst comprises a noble metal G, alumina, and a rare earth manganese-zirconium composite oxide. The noble metal G is dispersed at the grain boundaries and surface of the alumina and rare earth manganese-zirconium composite oxide, and the rare earth manganese-zirconium composite oxide has the general chemical formula RE. a Mn b Zr c M d O (2-δ) D β ;in, RE represents rare earth elements, M represents cation doping elements, and D represents anion doping elements. The doping element M is one or more of transition metal elements, alkaline earth metal elements, and Al, Si, and Sn. The doping element D includes one or more of anions N, P, and F. 0.1≤a≤0.5, 0.05≤b≤0.3, 0.2≤c≤0.8, 0≤d≤0.2, 0≤δ≤0.1, 0≤β≤0.1, a+b+c+d=1; The preparation method of the grain boundary and surface supported noble metal catalyst includes: S1. Mix rare earth manganese zirconium composite oxide and alumina with liquid salt of precious metal G evenly and then dry. S2. Perform one or two heat treatments on the product obtained in step S1. S3. The product obtained in step S2 is calcined once or twice under a reducing atmosphere to obtain rare earth manganese zirconium composite oxide and alumina grain boundary and surface supported noble metal catalyst.

2. A honeycomb-type noble metal catalyst, characterized in that, The catalyst comprises a honeycomb support, a noble metal G, and an active coating, wherein the active coating contains an alumina and a rare earth manganese-zirconium composite oxide RE. a Mn b Zr c M d O (2-δ) D β The noble metal G is dispersed at the grain boundaries and surface of the active coating; wherein, RE represents rare earth elements, M represents cation doping elements, and D represents anion doping elements. The doping element M is one or more of transition metal elements, alkaline earth metal elements, and Al, Si, and Sn. The doping element D includes one or more of anions N, P, and F. 0.1≤a≤0.5, 0.05≤b≤0.3, 0.2≤c≤0.8, 0≤d≤0.2, 0≤δ≤0.1, 0≤β≤0.1, a+b+c+d=1; The preparation method of the honeycomb noble metal catalyst includes: Rare earth manganese zirconium composite oxide and alumina, precious metal G liquid salt, acidity regulator, binder and water are mixed evenly in one or more steps to prepare a coating slurry. The slurry is coated onto the honeycomb carrier in one or more steps, or coated onto the honeycomb carrier in sections or layers, and then dried. The dried honeycomb carrier is then heat-treated and / or calcined under a reducing atmosphere to obtain a honeycomb type precious metal catalyst. The heat treatment temperature is 200-750℃ and the heat treatment time is 0.5-24h; the calcination temperature is 400-850℃ and the calcination time is 0.5-24h.

3. The catalyst according to claim 2, characterized in that, The rare earth manganese zirconium composite oxide accounts for 30-70% of the total mass of the active coating.

4. The catalyst according to any one of claims 1-3, characterized in that, The noble metal G at the grain boundaries and surface is in a metallic state, or in both a metallic and oxidized state.

5. The catalyst according to any one of claims 1-3, characterized in that, The precious metal G includes one or more of Pt, Pd, Rh, Ir, Os, Ru, Au and Ag.

6. The catalyst according to claim 5, characterized in that, The precious metal G includes one or more of Pt, Pd, Rh and Ru.

7. The catalyst according to claim 6, characterized in that, The precious metal G includes a combination of Pt and Pd.

8. The catalyst according to any one of claims 1-3, characterized in that, The rare earth elements RE include one or more combinations of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc.

9. The catalyst according to claim 8, characterized in that, The rare earth elements RE include one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Yb, and Y.

10. The catalyst according to claim 8, characterized in that, The transition metal element is one or more of Fe, Co, Ni, Cu, Zn, Ti, Hf, V, Cr, Nb, Mo, and W; the alkaline earth metal element is one or more of Mg, Ca, Sr, and Ba.

11. The catalyst according to claim 10, characterized in that, The transition metal element is one or more of Fe, Co, Ni, Cu and Hf; the alkaline earth metal element is one or more of Sr and Ba.

12. The grain boundary and surface-supported noble metal catalyst according to claim 1, characterized in that, The loading of precious metal G in this catalyst is 0.01%-2% by mass.

13. The grain boundary and surface-supported noble metal catalyst according to claim 12, characterized in that, The loading of precious metal G in this catalyst is 0.1% to 1% by mass.

14. The honeycomb noble metal catalyst according to claim 2, characterized in that, The loading of precious metal G in this catalyst is 0.03-2.0 g / L.

15. The honeycomb noble metal catalyst according to claim 14, characterized in that, The loading of precious metal G in this catalyst is 0.15-1.5 g / L.

16. The honeycomb noble metal catalyst according to claim 2, characterized in that, The cellular carrier is made of porous ceramic or metal.

17. The catalyst according to claim 1, characterized in that, The heat treatment temperature is 200-750 ℃, and the heat treatment time is 0.5-24h.

18. The catalyst according to claim 17, characterized in that, The heat treatment temperature is 400-700 ℃, and the heat treatment time is 1-12 h.

19. The catalyst according to claim 1, characterized in that, The roasting temperature is 400-850℃, and the time is 0.5-24h.

20. The catalyst according to claim 19, characterized in that, The roasting temperature is 450-750℃, and the time is 1-12h.

21. The catalyst according to any one of claims 1-3, characterized in that, The liquid salt of the precious metal G includes one or more of the following: molten salts or aqueous solutions of chlorides, nitrates, acetates, and citrates.

22. The catalyst according to any one of claims 1-3, characterized in that, The reducing atmosphere includes one or more of CO and H2.

23. The application of the catalyst as described in any one of claims 1-22 in the field of motor vehicle exhaust purification.

Citation Information

Patent Citations

  • Complex rare-earth oxidate containing valuable metal type honeycomb catalyst and its preparation

    CN1042092A

  • Catalyst material

    CN113661003A